Health impact of pain in the hip region with and without radiographic evidence of osteoarthritis: a study of new attenders to primary care - Birrell, F; Croft, P; Cooper, C; Hosie, G; Macfarlane, G; Silman, A; Grp, P (2000)
Objectives - To assess the health impact of hip pain at the time of first presentation to primary care, and the influence on this of radiographic evidence of osteoarthritis. Subjects and methods - Cross sectional survey of 195 patients (63 male, 132 female), aged 40 years and over, presenting with a new episode of hip pain, recruited from 35 general practices across the UK. Health status at presentation was determined by a structured questionnaire on symptoms, healthcare use, and health related quality of life (SF-36). Pelvic radiographs were assessed blindly for hip osteoarthritis using standard scoring systems. Results - The overall impact on health was substantial. Before their first consultation, three quarters of patients needed analgesics, half used topical creams or ointments, and one in eight used a walking stick. Most of these impact measures were, however, unrelated to the degree of radiographic change, though use of a walking stick was increased in those with the most severe damage. Health status, as judged by the SF-36, was also impaired for measures of physical function and pain, but the impact on the 'mental health', 'general health', and 'vitality' dimensions was small. There was a weak relation between the SF-36 scores and radiographic change, with many domains unrelated to the severity of radiographic damage. Conclusions - This study is the first to show the therapeutic impact and pattern of impairment in health status resulting from hip pain at the time of first presentation to the healthcare services. Unlike many regional pain syndromes seen in primary care, such as back pain, hip pain does not impact on wider aspects of quality of life, such as general health status, mental health, or vitality. Furthermore, any impact of hip pain in this group is not markedly influenced by the degree of structural damage. Further follow up is required to determine whether such damage influences the persistence of any adverse impact.